FAKTOR PENYEBAB PERILAKU AGRESIF SISWA MTsN 6 LIMA PULUH KOTA - Musfita Maisi; Dodi Pasilaputra; Alfi Rahmi; Hidayani Syam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Aggressive behavior among adolescents is one of the most common issues encountered in schools and has the potential to hinder students' social, emotional, and academic development. This phenomenon is still found among students at MTsN 6 Lima Puluh Kota, where aggressive behavior appears in both verbal and physical forms. This study aimed to describe the factors causing aggressive behavior among students at MTsN 6 Lima Puluh Kota. The research employed a qualitative approach with a descriptive research design. Informants were selected using purposive sampling and consisted of students, guidance and counseling teachers, homeroom teachers, and the Vice Principal for Student Affairs. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. Data credibility was ensured through source triangulation, technique triangulation, and time triangulation. The findings revealed that students' aggressive behavior was influenced by two main categories of factors, namely internal and external factors. Internal factors consisted of beliefs, genetic or family parenting patterns, emotions, and personality. Among these, beliefs and emotional instability were identified as the most dominant factors contributing to aggressive behavior. External factors included imitation, family environment, and community environment, with the family environment emerging as the strongest external influence. Inharmonious family communication, limited parental attention, and negative social interactions were found to contribute significantly to the development of aggressive behavior. The study concludes that aggressive behavior is the result of interactions between internal and external factors. Therefore, collaboration among schools, families, and communities is essential to create a supportive environment that can prevent and reduce aggressive behavior among students.